Crystallization and preliminary X-ray analysis of Atg10 - Yamaguti, Masaya (International Union of Crystallography, 2007)
Atg10 is an E2-like enzyme that catalyzes the conjugation reaction between Atg12 and Atg5. The Atg12–Atg5 conjugate is essential for autophagy, the bulk degradation process of cytoplasmic components by the vacuolar/lysosomal system. Microcrystals of Saccharomyces cerevisiae Atg10 were obtained by the free-interface diffusion method using polyethylene glycol and sodium acetate as precipitants. Using these precipitants, large crystals suitable for data collection were obtained using the sitting-drop vapour-diffusion method. The crystals belong to space group P4(1)2(1)2 or P4(3)2(1)2, with unit-cell parameters a = b = 51.61, c = 256.16 Å, and are estimated to contain two protein molecules per asymmetric unit. A native data set was collected to 2.3 Å resolution from a single crystal.